Mechatronic design of NAO humanoid - Gouaillier, David; Hugel, Vincent; Blazevic, Pierre; Kilner, Chris; Monceaux, Jerome; Lafourcade, Pascal; Marnier, Brice; Serre, Julien; Maisonnier, Bruno (2009 IEEE International Conference on Robotics and Automation, 2009)
This article presents the mechatronic design of the autonomous humanoid robot called NAO that is built by the French company Aldebaran-Robotics. With its height of 0.57 m and its weight about 4.5 kg, this innovative robot is lightweight and compact. It distinguishes itself from existing humanoids thanks to its pelvis kinematics design, its proprietary actuation system based on brush DC motors, its electronic, computer and distributed software architectures. This robot has been designed to be affordable without sacrificing quality and performance. It is an open and easy-to-handle platform. The comprehensive and functional design is one of the reasons that helped select NAO to replace the AIBO quadrupeds in the 2008 RoboCup standard league.